1997
DOI: 10.1016/s0014-5793(97)01205-2
|View full text |Cite
|
Sign up to set email alerts
|

Definitive chemical evidence for the constitutive ability of Candida albicans serotype A strains to synthesize β‐1,2 linked oligomannosides containing up to 14 mannose residues

Abstract: We have previously reported the presence of phosphate bound ß-1,2 linked oligomannosides with unusually high degrees of polymerization (DP > 7) in the mannan of Candida albicans strain VW32. To confirm this observation, we have prepared these oligomannosides from the mannan of C. albicans strain NIH A 207. Gel filtration chromatography and TLC analysis revealed DP up to 14. For both strains, NMR analysis confirmed the exclusive presence of ß-1,2 linkages in the pools of oligomannosides with a DP higher than 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
(51 reference statements)
1
31
0
Order By: Relevance
“…The stimulating activity of ␤-1,2- oligomannosides was found to depend on the length of the mannosyl chain and maximum activity was observed for DPs of 8 or higher (13). Interestingly, these high DPs are present mainly in the C. albicans PLM but correspond to minor components among the ␤-1,2-oligomannosides released from the mannan of the same species (24).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The stimulating activity of ␤-1,2- oligomannosides was found to depend on the length of the mannosyl chain and maximum activity was observed for DPs of 8 or higher (13). Interestingly, these high DPs are present mainly in the C. albicans PLM but correspond to minor components among the ␤-1,2-oligomannosides released from the mannan of the same species (24).…”
Section: Discussionmentioning
confidence: 95%
“…7 we suggest a structural model for the PLM glycan moiety, based on the first chemical evidence for the presence of ␤-1,2-linked oligomannosides in a glycoconjugate other than the yeast phosphopeptidomannan. Very little is known about ␤-1,2-mannosyltransferases of C. albicans, their activation and substrate specificity, but the presence of such linear chains of up to 18 mannose residues represent quite unusual structures (24). It has been suggested that a consequence of coating parasite surfaces with long sugar chains is the triggering of host effector mechanisms at a distance too great for efficient antimicrobial activity on the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These side chains in C. albicans consist of ␣1,2-and ␣1,3-linked mannose residues (20 -22) and in serotype A strains ␤1,2-linked mannose residues (23). The side chains and positions within the core are also modified by the addition of phosphomannan, consisting of a chain of ␤1,2-linked mannose residues attached via a phosphodiester bond (24). Previous studies in C. albicans have demonstrated the overall importance of glycosylation for cellular viability and virulence (25)(26)(27).…”
mentioning
confidence: 99%